Analisis Profil Atap Baja WF dengan Metode LRFD Menggunakan SAP 2000 dan Idea StatiCa - Pribadi, Gali; Rumbyarso, Yonas Prima Arga (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The roof is one of the main components in a building to protect it from heat and rain. The roof is also an architectural component that adds to the beauty of a building. Therefore, every building must have a roof. Currently, many steel roofs are used as the structural frame. Considering that wooden materials are considered expensive to use nowadays. Apart from that, steel material has a longer durability than wood material, so steel is considered the best alternative at the moment. The title of this article is